2021
DOI: 10.3390/insects12080704
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Profiles of Diploid Mutant Apis mellifera Embryos after Knockout of csd by CRISPR/Cas9

Abstract: In honey bees, complementary sex determiner (csd) is the primary signal of sex determination. Its allelic composition is heterozygous in females, and hemizygous or homozygous in males. To explore the transcriptome differences after sex differentiation between males and females, with genetic differences excluded, csd in fertilized embryos was knocked out by CRISPR/Cas9. The diploid mutant males at 24 h, 48 h, 72 h, and 96 h after egg laying (AEL) and the mock-treated females derived from the same fertilized que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 97 publications
(135 reference statements)
0
3
0
Order By: Relevance
“…On the other hand, the expression level of several specific female-biased genes was lower. Their data also confirmed that csd interacts with certain genes, such as fruitless, troponin T, and transformer-2 just to mention a few [81].…”
Section: Crispr-cas9 In Entomologymentioning
confidence: 61%
See 1 more Smart Citation
“…On the other hand, the expression level of several specific female-biased genes was lower. Their data also confirmed that csd interacts with certain genes, such as fruitless, troponin T, and transformer-2 just to mention a few [81].…”
Section: Crispr-cas9 In Entomologymentioning
confidence: 61%
“…The bees that are heterozygous at this specific locus are females, while the males are homozygous or hemizygous [80]. In a recent study, Wang et al (2021) [81] used the CRISPR-Cas9 tool in order to knock out the csd gene and, thus, eliminated the genetic difference between females and males. Subsequently, they aimed to observe the transcriptome difference between the two sexes in this particular genetic background.…”
Section: Crispr-cas9 In Entomologymentioning
confidence: 99%
“…Due to the easily accessible conditions for embryonic development (34°C temperature, 80% relative humidity) ( Nelson, 1915 ; Winston, 1987 ), the embryo is an ideal model used in honey bee genetic research ( DuPraw, 1967 ). Several works have been reported to understand honey bee embryonic development from describing morphology to dissecting molecular underpinnings, such as detailed morphological differentiation ( Fleig and Sander, 1986a ; Woyke, 1998 ; Katzav-Gozansky et al, 2003 ), transcriptional modification ( Pires et al, 2016 ; Netschitailo et al, 2022 ), and genome editing ( Kohno et al, 2016 ; Hu et al, 2019 ; Nie et al, 2021 ; Wang et al, 2021 ; Değirmenci et al, 2022 ). Recently, our works on proteomics elucidated that embryos at different ages have tailored distinct proteome arsenals to underline the age-specific physiological demands of honey bees ( Fang et al, 2014 ; Fang et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%